2018
DOI: 10.1093/abt/tby009
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers and Opportunities: Highlights of the 2nd Annual Conference of the Chinese Antibody Society

Abstract: The Chinese Antibody Society (CAS) convened the second annual conference in Cambridge, MA, USA on 29 April 2018. More than 600 members from around the world attended the meeting. Invited speakers discussed the latest advancements in therapeutic antibodies with an emphasis on the progress made in China. The meeting covered a vast variety of topics including the current status of therapeutic antibodies, the progress of immuno-oncology, and biosimilars in China. The conference presentations also included the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…HX009 consists of human IgG4-Fc of anti-PD-1 mAb and ECD of SIRPα, and can achieve the anti-tumor synergistic effects by simultaneously activating innate and adaptive immune responses and also by suppressing tumor immune escape by inhibiting the immune checkpoint [ 97 ]. The other candidate bispecific therapeutic, IBI322, was showed that its binding affinity to PD-L1 was stronger than that to CD47, implying a potential therapy to PD-L1-positive cancers [ 129 ].…”
Section: Bsab Molecules: Their Architectures and Moasmentioning
confidence: 99%
“…HX009 consists of human IgG4-Fc of anti-PD-1 mAb and ECD of SIRPα, and can achieve the anti-tumor synergistic effects by simultaneously activating innate and adaptive immune responses and also by suppressing tumor immune escape by inhibiting the immune checkpoint [ 97 ]. The other candidate bispecific therapeutic, IBI322, was showed that its binding affinity to PD-L1 was stronger than that to CD47, implying a potential therapy to PD-L1-positive cancers [ 129 ].…”
Section: Bsab Molecules: Their Architectures and Moasmentioning
confidence: 99%
“…Chinese companies are engaging with FDA, and developing their product candidates according to the standards of the FDA and the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (www.ich.org). 49 In particular, Chinese companies have progressed multiple antibodies targeting PD-1 into late-stage studies and regulatory review in China, including tislelizumab, sintilimab and camrelizumab.…”
Section: Antibody Therapeutics Undergoing Regulatory Review In Chinamentioning
confidence: 99%
“…Sintilimab achieved 77.6% of progression-free survival at 6 months for patients with cHL [ 1 ], and the efficacy appears to be comparable to that of nivolumab (77%) and pembrolizumab (69%) [ 2 , 3 ]. Dr. Michael Yu, the chairman, CEO and president of Innovent Biologics, commented that sintilimab, a novel full human IgG4 antibody targeting PD-1 generated by yeast display method, has 10–50 folds higher binding affinity to PD-1 than nivolumab and pembrolizumab [ 4 ] and pharmacodynamics analysis in cHL patients showed greater than 95% PD-1 receptor occupancy [ 1 ]. Based on the data of crystal structure of sintilimab/PD-1 complex [ 4 ], sintilimab appears to bind to PD-1 in a unique conformational epitope with highly complementary, hydrophobic surfaces formed by antibody complementarity-determining regions (CDRs), distinct from nivolumab and pembrolizumab.…”
mentioning
confidence: 99%
“…Dr. Michael Yu, the chairman, CEO and president of Innovent Biologics, commented that sintilimab, a novel full human IgG4 antibody targeting PD-1 generated by yeast display method, has 10–50 folds higher binding affinity to PD-1 than nivolumab and pembrolizumab [ 4 ] and pharmacodynamics analysis in cHL patients showed greater than 95% PD-1 receptor occupancy [ 1 ]. Based on the data of crystal structure of sintilimab/PD-1 complex [ 4 ], sintilimab appears to bind to PD-1 in a unique conformational epitope with highly complementary, hydrophobic surfaces formed by antibody complementarity-determining regions (CDRs), distinct from nivolumab and pembrolizumab. The area of the interactive hydrophobic surfaces on sintilimab is almost double those on nivolumab or pembrolizumab, with seven cluster-distributed alkyl–π interactions identified when bound to PD-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation